Greenness and its interaction with air pollution in relation to postmenopausal breast cancer risk in UK Biobank - Carmen Smotherman; Brian L. Sprague; Dejana Braithwaite; Lusine Yaghjyan (PLoS ONE, 2025)
It is unclear if natural vegetation (greenness) is associated with breast cancer breast cancer risk and if it interacts with air pollution. We investigated the associations of greenness with breast cancer risk in postmenopausal women, and the extent to which the association of the air pollutant PM 10 with breast cancer differs by greenness level. Of the 154,804 postmenopausal women included in the study, 6,131 developed breast cancer after the baseline assessment for enrollment into the UK Biobank. Data on greenness measures, and established breast cancer risk factors were available at baseline assessment (2006−2010), while data for PM 10 were available from 2007 and 2010. We used Cox proportional hazards models to assess adjusted associations between greenness and breast cancer risk. We also examined associations of PM 10 with breast cancer risk by greenness levels and their interactions. For each 0.1 unit increase in NDVI, we found a 2.6% increase in breast cancer risk (Hazard ratio [HR]=1.03, 95%CI 1.00–1.05). We also found evidence of a significant interaction, with stronger association between cumulative average PM 10 and breast cancer risk at lower NDVI levels (1 st quartile NDVI: HR per 10 µg/m 3 PM 10 = 3.03, 95%CI 1.98–4.64) versus higher NDVI levels (4 th quartile: HR = 1.52, 95%CI 1.16–1.98). We did not find interactions with other greenness measures. Our results suggest that various measures of greenness differ in their association with breast cancer and that there may be an interaction between greenness and PM 10 exposure in relation to breast cancer risk.